PENGARUH BEBAN KERJA DAN KESEJAHTERAAN TERHADAP KEPUASAN PEGAWAI BADAN PENGUSAHAAN BATAM - kurnia hardi, mardilla dwi; Wasiman (LPPM Universitas Putera Batam, 2022)
The purpose of the study was to determine the effect of workload and welfare on employee satisfaction at the Batam Business Board, using the saturated sample technique, in which all the population was sampled as many as 110 respondents who were employees of the Batam Business Board. The method of data collection is a questionnaire. The data quality test in this study uses validity and reliability tests, classical assumption tests and influence tests in this study using multiple linear regression analysis and analysis of the coefficient of determination (R2), while hypothesis testing in this study uses (t test) and (F test) by using the SPSS 25 software program. The coefficient of determination (R2) obtained from the workload and welfare variables has an effect of 70.1% on employee satisfaction. Multiple linear regression test results show that workload (X1) has an effect of 80.8% on employee satisfaction (Y) and welfare (X2) has an effect of 47.1% on employee satisfaction (Y). From the results of the t test and F test, it can be concluded that workload has a partially significant effect on employee satisfaction and welfare has a partially significant effect on employee satisfaction, and workload and welfare together have a significant simultaneous effect on employee satisfaction at the Batam Business Board. Keywords: Workload, Welfare, Employee Satisfaction.